2016
DOI: 10.46743/2160-3715/2016.2172
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Content Analysis of the Extent of Bloom’s Taxonomy in the Reading Comprehension Questions of the Course Book Q: Skills for Success 4 Reading and Writing

Abstract: Bloom’s taxonomy is probably the most commonly used one among the cognitive process models. It is a classification system that emphasizes the procedures starting from remembering the knowledge to more complex cognitive levels like evaluating the knowledge. Firstly, the aim of this study has been to find out to what extent Bloom’s taxonomy is referred in reading comprehension questions of an English as a Foreign Language course book. With this in mind, the research question To what extent do the reading section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 4 publications
2
24
0
1
Order By: Relevance
“…At these levels of processing, the cognitive strategies used, are different according to the domain-learning model ( Alexander, 2004 ) from basic coding to a transformation of the text. In the scientific literature, there are investigations ( Yussof et al, 2013 ; Ulum, 2016 ) that also identify levels of reading comprehension ranging from a literal level of identification of ideas to an inferential and critical level that require the elaboration of inferences and the data transformation.…”
Section: Introductionmentioning
confidence: 99%
“…At these levels of processing, the cognitive strategies used, are different according to the domain-learning model ( Alexander, 2004 ) from basic coding to a transformation of the text. In the scientific literature, there are investigations ( Yussof et al, 2013 ; Ulum, 2016 ) that also identify levels of reading comprehension ranging from a literal level of identification of ideas to an inferential and critical level that require the elaboration of inferences and the data transformation.…”
Section: Introductionmentioning
confidence: 99%
“…The two levels at the Guidance Level are the Recognizing and Remembering Details level and the Translation level. The other four levels at the Disappointed Stage are the Application, Analysis, Synthesis and Evaluation levels Ulum (2016). The Guidance Stage means that the student faces some problems in reading and comprehension material and still needs guidance, while the Disappointed Stage means that the student faces many problems in his reading and comprehension, and he feels frustrated to comprehend the reading material.…”
Section: Table 4 Results Of the Reading Comprehension Correlation Coef Icient Analysis With Student Achievementmentioning
confidence: 99%
“…The questions in reading comprehension exercises should be proportional among the low level cognitive questions and high level cognitive questions. The questions should be proportional because low and high cognitive questions are integrative (Freahat and Smadi in Ulum, 2016). Sukiman (2012) stated that the great composition for higher order thinking skill questions is 50% of the total number of questions.…”
Section: Higher Order Thinking Skillmentioning
confidence: 99%
“…The findings showed that about 40% of the textbook's questions emphasized higher order thinking skill. Ulum (2016) analyzed to what extent Bloom's Taxonomy is intended to in reading comprehension exercises questions of English as a Foreign Language textbook. This research finds that the book is lack of higher level thinking skill, the textbook only develops key cognitive skills such as remembering and understanding.…”
Section: Introductionmentioning
confidence: 99%